PENGARUH TATA KELOLA PERUSAHAAN DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Lalita, Alma; Rahayuningsih, Deasy Ariyanti (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2024)
The aim of this research is to obtain empirical evidence regarding the influence of managerial ownership, institutional ownership, board of directors, independent board of commissioners, audit committee, company size, company age, leverage and profitability on tax avoidance. This research is expected to provide insight, knowledge and references regarding factors affecting tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange as well as a guideline for testing that will be carried out in future research. This research is expected to provide information and insight to investors as a basis for making investment decisions related to variables that affect tax avoidance in manufacturing companies. The population that is the focus of this research includes 83 manufacturing companies listed on the Indonesia Stock Exchange during the period 2019 to 2021. In this research, the sample used was 249 data. The sampling technique uses a purposive sampling method. The hypothesis was tested using the multiple regression method. The empirical results of this research show that the audit committee, leverage and profitability have an influence on tax avoidance. Apart from that, other variables such as managerial ownership, institutional ownership, board of directors, independent board of commissioners, company size and company age have no influence on tax avoidance.